2016
DOI: 10.1097/jcp.0000000000000435
|View full text |Cite
|
Sign up to set email alerts
|

Does Insight Affect the Efficacy of Antipsychotics in Acute Mania?

Abstract: Patients having an acute manic episode of bipolar disorder often lack insight into their condition. Because little is known about the possible effect of insight on treatment efficacy, we examined whether insight at the start of treatment affects the efficacy of antipsychotic treatment in patients with acute mania. We used individual patient data from 7 randomized, double-blind, placebo-controlled registration studies of 4 antipsychotics in patients with acute mania (N = 1904). Insight was measured with item 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A very important posthoc analysis of individual patient data reported that patients with impaired insight (as measured with the use of item 11 of the YMRS) responded better; therefore treatment should be initiated immediately and the therapist should not wait until the patient gains sufficient insight (Welten et al, 2016). …”
Section: Efficacy Datamentioning
confidence: 99%
“…A very important posthoc analysis of individual patient data reported that patients with impaired insight (as measured with the use of item 11 of the YMRS) responded better; therefore treatment should be initiated immediately and the therapist should not wait until the patient gains sufficient insight (Welten et al, 2016). …”
Section: Efficacy Datamentioning
confidence: 99%
“…The post hoc analysis (as conducted by Welten et al, 2016 ) of both studies pooled showed that baseline level of insight significantly modified the efficacy of treatment as measured by YMRS mean change score ( p = 0.0013) and response rate ( p = 0.0298), with greater improvement in patients with “impaired” or “no insight” than in patients with “excellent insight.”…”
Section: Resultsmentioning
confidence: 99%
“…When pooling the studies and presenting baseline insight scores by region, a total of 282 (63.2%) US patients had “excellent insight,” 101 (22.6%) had “good insight,” 40 (9.0%) had “moderate insight,” 17 (3.8%) had “poor insight,” and six (1.3%) had “no insight.” Thus, insight was impaired or absent (as defined by Welten et al, 2016 ) in 36.8% of the US patients. In contrast, insight was impaired or absent in 95.1% of the EU patients: 10 (4.9%) EU patients had “excellent insight,” 52 (25.6%) had “good insight,” 90 (44.3%) had “moderate insight,” 44 (21.7%) had “poor insight,” and seven (3.4%) had “no insight.”…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations